2005
DOI: 10.3844/ajbbsp.2005.167.172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Tospovirus Transmitting Thrips Populations from India

Abstract: The presence of Tospovirus in thrips vector, Scirtothrips dorsalis has been detected for the first time in India using RT-PCR analysis. Similarly RT-PCR analysis with GBNV infected tomato leaves also resulted in the amplification of cDNA corresponding to the N gene (approximately 830 bp) of Coimbatore isolate. Dendrogram constructed on the basis of RAPD similarity matrix revealed that S. dorsalis population from tomato, groundnut and chillies had atleast 75% similarity while; only 50 % similarity existed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This pest damages its host by feeding on the young leaves, buds, and fruits resulting in feeding scars, color distortions, and stunted growth (Seal et al 2005, 2006). Scirtothrips dorsalis is the only Scirtothrips species known to be a vector of certain Tospoviruses which include Groundnut bud necrosis virus , Peanut chlorotic fanspot virus , and Peanut yellow spot virus (Whitfield et al 2005; Meena et al 2005; Moritz et al 2000). This species of thrips has a habitat that is widespread ranging from temperate to tropical climatic regions.…”
Section: Introductionmentioning
confidence: 99%
“…This pest damages its host by feeding on the young leaves, buds, and fruits resulting in feeding scars, color distortions, and stunted growth (Seal et al 2005, 2006). Scirtothrips dorsalis is the only Scirtothrips species known to be a vector of certain Tospoviruses which include Groundnut bud necrosis virus , Peanut chlorotic fanspot virus , and Peanut yellow spot virus (Whitfield et al 2005; Meena et al 2005; Moritz et al 2000). This species of thrips has a habitat that is widespread ranging from temperate to tropical climatic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few hundred of the 5,500 identified thrips species are pests (Brunner et al 2002), and of these, only 14 are documented virus vectors (Riley et al 2011). Chilli thrips Scirtothrips dorsalis is both a virus vector (Chu et al 2001; Meena et al 2005; Gopal et al 2010) and a pest of many crops around the world including tea (Saha & Mukhopadhyay 2013), mango (Aliakbarpour & Md. Rawi 2012; Choi et al 2013), roses (Hegde et al 2011; Mannion et al 2013), and citrus (Gao et al 2012; Hyun et al 2012).…”
mentioning
confidence: 99%
“…Earlier reports suggested that thrips like S. dorsalis (German et al, 1992;Meena et al, 2005), T. palmi (Lakshmi et al, 1995;Meena et al, 2005;Reddy et al, 1992) and F. schultzei (Meena et al, 2005) were observed as putative vectors for GBNV, whereas T. tabaci could transmit Tomato spotted wilt virus (TSWV) (Wijkamp et al, 1995). In NCBI few entries were available related to Tusothrips sumatrensis and T. apicatus.…”
Section: Resultsmentioning
confidence: 99%